Quality of nursing work life among staff nurses in a tertiary care hospital in Puducherry - Venkataraman, Surendran; Anbazhagan, Suguna; Anbazhagan, Surekha (International Journal Of Community Medicine And Public Health, 2018)
Background: Quality of nursing work life (QNWL) is degree to which nurses can satisfy important personal needs through their experiences in work organization, while achieving the organization's goals, to make meaningful contributions to their organization. Objectives of the study were to assess the quality of nursing work life among staff nurses in a tertiary care hospital in Puducherry and to study the influence of socio-demographic factors on the QNWL of these staff nurses. Methods: We conducted a cross-sectional analytical study in a tertiary care hospital in Puducherry between January and June 2017. Based on universal sampling, all 429 nurses with more than one-year work experience were selected for the study. After obtaining Ethical approval from the institution and informed consent from the study participants, data on socio-demographic characteristics, work-related information and QNWL were collected using a semi-structured questionnaire. Double data entry was done in Epidata entry client (v4.2.0) and analysed using STATA (v14) software. Results: Among the nurses, 90% were females and 60% were from rural background. The study revealed that there was a moderate QNWL score reported among majority (60%) of staff nurses. Bivariate analysis showed higher the age, female gender, absence of dependent individuals at home, higher income, more work experience, having only a diploma degree, working in OPDs and no nightshifts were the significant factors contributing to higher QNWL scores (p<0.05). Conclusions: The study identified factors that influence the nurses’ work life quality which can be used for developing and appropriately implementing successful induction programs to improve the QNWL.